Design and analysis of distributed denial of service (DDOS) attack-aware link assignment in software defined networking - Ali, Sameer (2021)
A Software Defined Networking (SDN) is a modern networking paradigm with its three tier horizontal architecture. The great innovation in this network is that, it decouples the control plane from the data plane. SDN structure allows network to be managed and organized centrally from control logic and can be easily accessible to the network administrators, engineers and network operators. However, it is susceptible to attacker’s Distributed Denial of Service (DDoS) attacks. DDoS attacks are the main causes of disabling SDN network; drain-off network services to end-users by flooding network traffic using malicious botnets to SDN. Subsequently, it has a crucial impact on network performance. The availability of the network may be completely loss if a controller has failed due to DDoS attack. Controller and switch communication depends upon links assigned. The controller will be unable to process the traffic requests if links failed between controller and switches due to DDoS attack. Hitherto, link assignment for SDN switches to controllers only consider capacity of links between controllers and switches without taking DDoS into consideration at planning stage. Hence, DDoS which is part of network security issues require urgent attention. This thesis focuses on deriving exact methods to establish the backup link assignments from switches to controllers in a network for the planning problem of SDN network. A mathematical model, referred to as the planning model, is proposed that decides the optimal placement of the links between switches and controllers on a network while minimizing the overall cost. The advantages of the proposed models are to incorporate realistic constraints. A solver optimizes the exact method for the model with many scenarios and the results are compared.